Polyamide organic solvent nanofiltration membrane and preparation method thereof

PEI+PPD/TMC membrane was prepared by isopropanol-assisted interfacial polymerization method, which solved the problems of low permeability of organic solvent nanofiltration membrane and high cost of amine solvents, and achieved a high permeability and stable polyamide membrane, suitable for organic Solvent nanofiltration and wastewater treatment.

CN119258818APending Publication Date: 2025-01-07NORTHEAST FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411666987.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing polymer organic solvent nanofiltration membrane has low permeability in organic solvent systems and is difficult to operate stably for a long time, which limits its industrial application. The commonly used amine solvents are costly and have high toxicity, which limits its wide application.

Method used

Isopropanol is used as the amine monomer solvent, and polyamide organic solvent nanofiltration membrane is prepared by reacting with polyethyleneimine and p-phenylenediamine in isopropanol solution and crosslinking with phenylenediyl chloride in n-hexane. , forming a high-performance PEI+PPD/TMC film.

Benefits of technology

High solvent flux and excellent retention performance were achieved, and the ethanol permeability flux reached 46.44L·m-2·h-1·bar-1, the retention rate of active drugs and dyes was high, and it was maintained in polar solvents. Stability provides a simple high permeability and stable polyamide film preparation strategy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258818A_ABST
    Figure CN119258818A_ABST
Patent Text Reader

Abstract

The invention discloses a polyamide organic solvent nanofiltration membrane and a preparation method thereof, and belongs to the technical field of membrane separation. Isopropyl alcohol with polarity and swelling property is used as an amine monomer solvent to dissolve two polyamine molecules of polyethyleneimine with a flexible structure and p-phenylenediamine with a rigid structure; and cross-linking with trimesoyl chloride in normal hexane to obtain the polyamide membrane. According to the composite membrane prepared by the method, a loose separation layer is constructed to obtain high solvent flux, meanwhile, excellent interception performance is kept in an organic solvent nanofiltration experiment, and a simple and convenient strategy is provided for a high-permeability and stable polyamide membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane separation, and in particular relates to a polyamide organic solvent nanofiltration membrane and a preparation method thereof. Background Art

[0002] Membrane separation technology has attracted much attention for its advantages such as simplicity, high efficiency, low temperature, easy large-scale production, energy saving and environmental protection. It has been widely used in various fields such as petrochemicals, food, pharmaceuticals, metallurgy, sewage treatment, and traditional Chinese medicine concentration and purification. Among them, organic solvent filtration (OSN) is indispensable. Compared with traditional methods such as distillation and evaporation, OSN has the advantages of no phase change, high efficiency, and greenness. In addition, OSN can be combined with traditional separation technologies to form a hybrid separation process, thereby increasing overall flexibility. Therefore, OSN has great application potential in production fields involving organic solvent systems, such as separation of active pharmaceutical ingredients from organic solutions, catalyst recovery, and edible oil extraction. However, OSN membranes still have problems such as low permeability and difficulty in long-term stable operation in solvent systems, which limits their industrial application. In recent years, a lot of research has been conducted to expand the properties of membranes to develop new applications, and high-performance OSN films have been designed by adopting new monomers and innovative membrane preparation schemes. In order to obtain swelling-resistant and stable OSN films, chemical crosslinking is widely used. However, there is a trade-off between the permeability and selectivity of polymer OSN membranes. To this end, people have carried out a lot of research to solve this problem. Graphene oxide (GO) interlayers, metal organic frameworks (MOFs), carbon nanotubes (CNTs), covalent organic frameworks (COFs), etc. are usually used to improve the performance of OSN membranes. Among them, interfacial polymerization is based on a porous support layer. The polyamide thin film composite (TFC) membrane prepared by interfacial polymerization forms a uniform and dense polyamide (PA) layer through the polymerization of amine and acyl chloride monomers at the interface of the two phases, thereby giving the separation layer solvent resistance and good separation performance. It has attracted widespread attention. TFC membranes can effectively intercept small organic molecules with a molecular weight within a specific range. In the process of organic solvent nanofiltration, the membrane material needs to withstand the erosion of various organic solvents. This ability of polyamide membranes is suitable for application in complex experimental environments such as organic solvent nanofiltration.

[0003] There are many factors that affect the interfacial polymerization (IP) reaction, such as monomer concentration, cross-linking temperature, surfactant type, organic phase solvent type, chemical properties and microstructure of the substrate, type and concentration of additives, etc. Increasing the monomer concentration and cross-linking temperature can generally increase the degree of cross-linking of the interfacial layer, thereby improving the selectivity of the membrane. Surfactants affect the interfacial tension between the aqueous phase and the organic phase, thereby affecting the diffusion rate of the monomer and the IP reaction rate. For example, Chen found that the self-assembled chains of surfactants aggregate and pre-assemble monomers at the oil-water interface and improve their interphase transport. This promotion process saves more than 72-48h of polymerization and crystallization time costs, and improves crystallinity and pore uniformity, thereby having ultra-high permeability to acetonitrile. Parameters such as viscosity and surface tension of the organic phase solvent will directly affect the diffusion rate of amine monomers into the organic phase. For example, Zheng et al. used ionic liquids instead of traditional solvents for the organic phase, thereby limiting the diffusion rate of the organic phase and improving membrane performance. Adding a cosolvent to the organic phase is also one of the commonly used methods. For example, Fu et al. proposed using acetone as an organic phase cosolvent. The addition of acetone increased the width of the IP reaction zone, and the resulting membrane showed a 2.6-fold higher permeability of methanol solvent. Kamada et al. studied the addition of cosolvents such as acetone, ethyl acetate, ether, toluene, isopropanol (IPA) and N,N'-dimethylformamide (DMF) to the organic phase solution to regulate the surface morphology and polyamide network structure of the TFC membrane. They found that when 3wt% ethyl acetate was added to the organic phase, the NaCl rejection rate was greater than 99% and the water flux could be increased by three times. Huang and McCutcheon obtained a TFC-FO membrane with better performance by adding acetone to the organic phase. Kim et al. added triphenyl phosphate (TPP) and tributyl phosphate (TBP) to the organic phase solution and found that the water flux of the TFC membrane increased significantly and the desalination rate decreased slightly. The above researchers reported that the addition of isopropanol has a significant effect on the performance of nanofiltration membranes, but isopropanol is mostly added in the organic phase to dissolve acyl chloride monomers, replacing traditional n-hexane solvents, while the present invention utilizes isopropanol as an amine monomer solvent. In contrast, it is a more efficient and simple method. In recent years, a large number of relevant literature reports have been made that in traditional interfacial polymerization processes, commonly used amine solvents such as ethylenediamine, ionic liquids, etc. are used to modify the membrane surface to improve its hydrophilicity and ability to block impurities. However, these conventional amine solvents may have problems such as high cost of use and high toxicity in some cases, which limits their widespread application in industry. Therefore, it is particularly important to find an economical, efficient and environmentally friendly alternative amine solvent. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a polyamide organic solvent nanofiltration membrane and a preparation method thereof.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a polyamide organic solvent nanofiltration membrane comprises the following steps: weighing polyethyleneimine, p-phenylenediamine and sodium dodecylbenzenesulfonate, adding them into an isopropanol solution, and ultrasonically treating them until dissolved to obtain an amine solution; soaking a dried HPAN support membrane in the amine solution for reaction, taking it out and drying it at room temperature;

[0007] The dried membrane is placed in a n-hexane solution of trimesoyl chloride for reaction, and then taken out for cross-linking reaction to obtain a polyamide organic solvent nanofiltration membrane.

[0008] Preferably, the preparation method comprises the following steps:

[0009] 1) adding polyacrylonitrile and polyvinyl pyrrolidone to N,N-dimethylformamide solution for dissolution to obtain a light yellow transparent viscous liquid; allowing the light yellow transparent viscous liquid to stand at room temperature for defoaming to form a uniform casting solution; pouring the casting solution on a non-woven fabric to form a film, and immersing the film in deionized water to form a PAN film; immersing the PAN film in a NaOH solution for hydrolysis to obtain an HPAN film; rinsing the HPAN film with deionized water until it becomes neutral, thereby obtaining an HPAN support film;

[0010] 2) Weighing polyethyleneimine, p-phenylenediamine and sodium dodecylbenzenesulfonate, adding them to an isopropanol solution, ultrasonically treating until dissolved, to obtain an amine solution; immersing a dried HPAN support membrane in the amine solution for reaction, taking it out and drying it at room temperature; dissolving trimesoyl chloride in n-hexane to obtain a trimesoyl chloride solution; placing the dried membrane in the trimesoyl chloride solution for reaction, taking it out and performing a cross-linking reaction, to obtain a polyamide organic solvent nanofiltration membrane, recorded as PEI+PPD / TMC.

[0011] Furthermore, the hydrolysis refers to hydrolysis at 50° C. for 1 h.

[0012] Furthermore, the amount of polyethyleneimine added is based on the concentration of polyethyleneimine in the isopropanol solution being 1-5wt%; the amount of p-phenylenediamine added is based on the concentration of p-phenylenediamine in the isopropanol solution being 1-3wt%; and the amount of sodium dodecylbenzene sulfonate added is based on the concentration of sodium dodecylbenzene sulfonate in the isopropanol solution being 0.1wt%.

[0013] Preferably, the concentration of polyethyleneimine in the isopropanol solution is 3-5 wt %; more preferably 3 wt %.

[0014] Preferably, the concentration of p-phenylenediamine in the isopropanol solution is 1-3 wt %; more preferably 2 wt %.

[0015] Preferably, the concentration of the trimesoyl chloride solution is 0.05-0.25 wt %; more preferably, the concentration of the trimesoyl chloride solution is 0.1-0.2 wt %; more preferably, the concentration of the trimesoyl chloride solution is 0.15 wt %.

[0016] Furthermore, the HPAN support membrane reacts in the amine solution for 10 minutes.

[0017] Furthermore, the dried film was reacted in a n-hexane solution of trimesoyl chloride for 10 min.

[0018] The cross-linking reaction is carried out at 80° C. for 10 minutes.

[0019] The present invention also provides a polyamide organic solvent nanofiltration membrane prepared by the preparation method.

[0020] The present invention also provides an application of the polyamide organic solvent nanofiltration membrane in wastewater treatment, which is mainly used for treating organic dyes in wastewater.

[0021] Compared with the prior art, the present invention has the following advantages and technical effects:

[0022] The present invention uses isopropanol as an alternative amine solvent, which has the advantages of low cost, low toxicity and easy availability. The present invention uses isopropanol with polarity and swelling properties as an amine monomer solvent to dissolve two polyamine molecules, polyethyleneimine with a flexible structure and p-phenylenediamine with a rigid structure, and cross-links them with trimesoyl chloride in n-hexane to obtain a polyamide membrane. The composite membrane prepared by this method constructs a loose separation layer to obtain a high solvent flux while maintaining excellent retention performance in an organic solvent nanofiltration experiment. The prepared PEI+PPD / TMC membrane has excellent solvent permeability, and the ethanol permeation flux can reach 46.44L·m - 2 ·h -1 bar -1 . At the same time, the PEI+PPD / TMC membrane can achieve a retention rate of 88.19% for the active drug molecule sodium fluorescein, and the retention rates for the dyes RB, CR, AF, EBT, and Calcein are 96.63%, 95.98%, 95.21%, 93.84%, and 85.79%, respectively, showing good selectivity. In addition, the PEI+PPD / TMC membrane has good stability in polar solvents. The present invention provides a simple strategy for highly permeable and stable polyamide membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0024] Figure 1 This is a flow chart of the preparation of the PEI+PPD-TMC membrane in the embodiment;

[0025] Figure 2 The physicochemical and surface properties of different films in Example 1 and Comparative Examples 1-2; (a) ATR-FTIR spectrum of PEI+PPD-TMC film, wave number 500-1700cm -1 ; (b) is the ATR-FTIR spectrum of PEI+PPD-TMC film; (c) is the full spectrum of PEI+PPD-TMC film, (d) is the C1s peak of PEI+PPD-TMC film, (e) is the N1s peak of PEI+PPD-TMC film, (f) is the O1s peak of PEI+PPD-TMC film; (g) is the water contact angle of PEI / TMC, PPD / TMC and PEI+PPD / TMC; (h) is the ethanol contact angle of PEI / TMC, PPD / TMC and PEI+PPD / TMC; (i) is the Zeta potential of PEI+PPD / TMC film;

[0026] Figure 3 SEM images of the surfaces and cross-sections of different TFC membranes; (a) is the surface SEM image of PEI / TMC membrane; (b) is the surface SEM image of PPD / TMC membrane; (c) is the SEM image of PEI+PPD / TMC membrane at 0.15wt% TMC concentration; (d) is the SEM image of PEI+PPD / TMC membrane at 0.05wt% TMC concentration; (e) is the SEM image of PEI+PPD / TMC membrane at 0.25wt% TMC concentration; (f) is the cross-section of PEI+PPD / TMC membrane at 0.15wt% TMC concentration; (g) is the cross-section of PEI+PPD / TMC membrane at 0.05wt% TMC concentration; (h) is the cross-section of PEI+PPD / TMC membrane at 0.25wt% TMC concentration; (i) is the AFM image of PEI+PPD / TMC at 0.15wt% TMC concentration;

[0027] Figure 4The effects of different conditions on the performance of TFC membranes; (a) the effects of different solvents on the performance of PEI+PPD / TMC membranes; (b) the effects of different PEI concentrations on the performance of PEI+PPD / TMC membranes; (c) the effects of different PPD concentrations on the performance of PEI+PPD / TMC membranes; (d) the effects of different TMC concentrations on the performance of PEI+PPD / TMC membranes; (e) the UV absorption spectrum of the best membrane for AF retention; (f) the mechanism diagram of isopropanol as a swelling agent;

[0028] Figure 5 The separation performance of different TFC membranes; (a) comparison of the properties of PEI / TMC, PPD / TMC and PEI+PPD / TMC membranes with acid fuchsin in EtOH; (b) the permeation flux and retention rate of PEI+PPD / TMC membrane for different dyes / EtOH; (c) schematic diagram of the separation of AF and MO mixed dyes; (d) UV spectrum of the separation performance of AF and MO mixed dyes; (e) UV spectrum of the separation performance of sodium fluorescein; (f) UV spectrum of the separation performance of chlorogenic acid; (g) UV spectrum of the separation performance of berberine hydrochloride and sodium fluorescein; (h) flux of different solvents through PEI+PPD / TMC membrane; (i) linear correlation curve between solvent permeability and 1 / η of PEI+PPD / TMC membrane;

[0029] Figure 6 Figure 2 shows the stability of PEI+PPD / TMC membrane; (a) a long-term separation experiment with an operation time of 500 minutes; (b) the changes in membrane retention rate and permeation flux of RB under different operating pressures; (c) a cyclic stability experiment; (d) the separation performance of EBT in different solvents; (e) a schematic diagram of the separation mechanism; (f) a comparison of infrared spectra before and after long-term separation of the membrane; (g) a scanning electron microscope image of the membrane surface morphology before immersion in EtOH for 7 days; (h) a scanning electron microscope image of the membrane surface morphology after immersion in EtOH for 7 days; (i) a comparison of OSN performance reported in the literature. DETAILED DESCRIPTION

[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0031] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0035] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0036] Materials required for the following examples of the present invention: polyacrylonitrile (average molecular weight 85000), polyvinyl pyrrolidone (average molecular weight 10000), N', N-dimethylformamide (DMF, AR99.5%), polyethyleneimine (PEI, average molecular weight MW10000, 99%), p-phenylenediamine (PPD, 98%), sodium dodecylbenzenesulfonate (SDBS, AR 90%), trimesoyl chloride (TMC, 99.09%) and sodium hydroxide (NaOH, AR 95%). The organic solvents used in the experiment, including n-hexane, methanol (MeOH), ethanol (EtOH), isopropanol (IPA), ethyl acetate (EA), acetone (ACE), n-butanol (NBA) and ethylene glycol (EG) are all analytically pure and come from Tianjin Fuyu Reagent. The dyes used in the experiment include Bengal red (RB), Congo red (CR), acid fuchsin (AF), chrome black T (EBT), methyl orange (MO), and calcein (Calcein) from Shanghai Yien. Small molecule drugs including fluorescein sodium (FLS, AR 98%), berberine hydrochloride (AR 98%), and chlorogenic acid standards are sourced from Shanghai Yuanye.

[0037] Characterization required for the following examples: The morphology of the TFC films was observed by field emission scanning electron microscopy (SEM, EM-30plus) and atomic force microscopy (AFM, Dimension Icon). All samples were sputter-coated with a thin layer of Au / Pd to enhance their conductivity before SEM observation. Fourier transform infrared (FTIR) spectra were collected on an IS10 spectrometer with a wave number range of 400-4000 cm -1 The attenuated total reflection (ATR) mode was used for film testing in the range of 1000 nm. The contact angle of ethanol and water was measured with DSA100S at room temperature. X-ray photoelectron spectrometer (XPS) was from Thermo Scientific ESCALAB250Xi. The zeta potential of the film was carried out by streaming potential method on SurPASS electrokinetic analyzer (Anton Paar GmbH). Thermogravimetric analysis (TGA) curves were obtained by NETZSCH STA449 F3 to characterize the thermal stability of the film. The UV-visible spectrum of PEI+PPD / TMC nanofiltration membrane was measured using a UV-visible spectrophotometer (TU-1901).

[0038] The technical solution of the present invention is further illustrated by the following embodiments.

[0039] Example 1

[0040] 1) Preparation of HPAN support membrane:

[0041] 1.5 g of polyacrylonitrile (PAN) and 0.546 g of polyvinyl pyrrolidone (PVP) were added to 12.23 mL of N,N-dimethylformamide (DMF) solution and dissolved on a magnetic stirrer until a light yellow transparent viscous liquid was obtained; the light yellow transparent viscous liquid was allowed to stand at room temperature to defoam and form a uniform casting solution; the casting solution was poured onto a clean non-woven fabric and evenly moved with a glass rod to form a uniform film on the non-woven fabric. After 20 seconds, the scraped film was quickly immersed in 2 L of deionized water, and the DMF solvent was quickly exchanged with water, which eventually caused the polymer to precipitate and solidify to form a supporting base film (PAN film); the PAN film was immersed in a 2 M NaOH solution and hydrolyzed at 50 ° C for 1 hour to obtain a hydrolyzed PAN film (referred to as HPAN film); the HPAN film was rinsed with deionized water until it became neutral, i.e., the HPAN support film was obtained, which was stored in deionized water for use.

[0042] 2) Preparation of PEI+PPD-TMC membrane

[0043] The membrane preparation process is as follows Figure 1 shown.

[0044] Weigh polyethyleneimine (PEI), p-phenylenediamine (PPD), and sodium dodecylbenzene sulfonate (SDBS) in a beaker, add isopropanol solution (the amount of polyethyleneimine added is based on the concentration of polyethyleneimine in the isopropanol solution being 3wt%; the amount of p-phenylenediamine added is based on the concentration of p-phenylenediamine in the isopropanol solution being 2wt%; the amount of sodium dodecylbenzene sulfonate added is based on the concentration of sodium dodecylbenzene sulfonate in the isopropanol solution being 0.1wt%) and perform ultrasonic treatment until dissolved to obtain amine solution; soaking the dried HPAN substrate in an amine solution for reaction for 10 minutes, taking it out and drying it in air at room temperature for 5 minutes; dissolving trimesoyl chloride (TMC) in n-hexane to obtain a 0.15wt% trimesoyl chloride solution; placing the dried membrane in the trimesoyl chloride solution for reaction for 10 minutes, taking it out and placing it in an oven at 80°C for cross-linking for 10 minutes to obtain PEI+PPD / TMC (named M1); rinsing it and soaking it in ethanol (EtOH) for storage.

[0045] When trimesoyl chloride (TMC) was dissolved in n-hexane to obtain a 0.05 wt % trimesoyl chloride solution, the prepared PEI+PPD / TMC was named M3;

[0046] When trimesoyl chloride (TMC) is dissolved in n-hexane to obtain a 0.25 wt % trimesoyl chloride solution, the prepared PEI+PPD / TMC is named M5.

[0047] Comparative Example 1

[0048] 1) The preparation of HPAN support membrane is the same as in Example 1;

[0049] 2) Preparation of PEI / TMC membrane:

[0050] Weigh polyethyleneimine (PEI) and sodium dodecylbenzene sulfonate (SDBS) in a beaker, add isopropanol solution (the amount of polyethyleneimine added is based on the concentration of polyethyleneimine in the isopropanol solution being 3wt%; the amount of sodium dodecylbenzene sulfonate added is based on the concentration of sodium dodecylbenzene sulfonate in the isopropanol solution being 0.1wt%) and ultrasonically treat until dissolved to obtain an amine solution; soak the dried HPAN substrate in the amine solution for reaction for 10 minutes, take it out and dry it in air at room temperature for 5 minutes; dissolve trimesoyl chloride (TMC) in n-hexane to obtain a 0.15wt% trimesoyl chloride solution; place the dried film in the trimesoyl chloride solution for reaction for 10 minutes; take it out and put it in an oven at 80°C for cross-linking for 10 minutes to obtain PEI / TMC; rinse it and soak it in ethanol (EtOH) for storage.

[0051] Comparative Example 2

[0052] 1) The preparation of HPAN support membrane is the same as in Example 1;

[0053] 2) Preparation of PPD / TMC membrane:

[0054] Weigh p-phenylenediamine (PPD) and sodium dodecylbenzene sulfonate (SDBS) in a beaker, add isopropanol solution (the amount of p-phenylenediamine added is based on the concentration of p-phenylenediamine in the isopropanol solution being 2wt%; the amount of sodium dodecylbenzene sulfonate added is based on the concentration of sodium dodecylbenzene sulfonate in the isopropanol solution being 0.1wt%) and ultrasonically treat until dissolved to obtain an amine solution; soak the dried HPAN substrate in the amine solution for reaction for 10 minutes, take it out and dry it in air at room temperature for 5 minutes; dissolve trimesoyl chloride (TMC) in n-hexane to obtain a 0.15wt% trimesoyl chloride solution; place the dried film in the trimesoyl chloride solution for reaction for 10 minutes; take it out and put it in an oven at 80°C for cross-linking for 10 minutes to obtain PPD / TMC; rinse it and soak it in ethanol (EtOH) for storage.

[0055] The named raw material variables of the polyamide thin film composite membrane (TFC membrane) obtained in Example 1 and Comparative Examples 1-2 are shown in Table 1.

[0056] Table 1 Naming conventions for preparing monomers and a series of TFC membranes

[0057]

[0058]

[0059] Performance Testing:

[0060] Separation performance of TFC membrane: The permeability and dye retention rate of the flat membrane (TYLG-17) produced by Shandong Bona Biotechnology Group Co., Ltd. were measured. The device consists of a pump, a membrane tank, a regulator, a pressure gauge and a pipe rack. The effective filtration area of ​​the device is 2.54 cm 2 All membranes were pre-pressed with ethanol at 2 bar until a stable permeability was reached before testing. This experiment was performed at room temperature. Each experiment should be performed at least three times in parallel. The pure water permeability (Jw, L·h -1 ·m -2 bar -1 ) is defined as follows:

[0061] Where P (bar) is the test pressure, V (L) is the permeate volume, A (m 2 ) is the effective filtration area, and Δt (h) is the collection time. The membrane retention rate was determined using dyes such as acid fuchsin (AF), methyl orange (MO), sodium fluorescein (AR 98%), and berberine hydrochloride (AR 98%). Each dye solution was selected at 10 mg·L -1 The concentration of the dye was dissolved in ethanol for testing. The mixed dye contained 10 mg·L -1 AF and 10 mg·L -1 MO. The mixed drug molecule contains 5 mg·L -1 10mg L -1 Sodium fluorescein. A UV-visible spectrophotometer (TU-1901) was used to determine the concentration of dye and drug. The dye and drug rejection rate (R, %) was calculated as follows:

[0062]

[0063] where Cf and Cp represent the concentrations of feed solution and permeate, respectively.

[0064] Test results:

[0065] 1. Surface physical and chemical properties of PEI / TMC, PPD / TMC, and PEI+PPD / TMC membranes (M1)

[0066] Figure 2 The physicochemical and surface properties of different films in Example 1 and Comparative Examples 1-2 are shown. Figure 2 (a) is the ATR-FTIR spectrum of PEI+PPD-TMC film, with wavenumbers between 500-1700cm -1 between, Figure 2 (b) is the ATR-FTIR spectrum of PEI+PPD-TMC film with wavenumbers between 1700-4000cm-1 As can be seen from the figure, compared with the HPAN substrate, the PEI+PPD / TMC membrane prepared by IP has a -1 A new peak is shown at 1404 cm -1 The peak at 1254 cm corresponds to the characteristic peak of amide NH in the membrane, and this weak signal may be due to the fact that the surface of the TFC membrane formed by IP is covered by a thin polyamide layer. In addition, due to the addition of SDBS surfactant with sulfonic acid groups during the preparation process, for the PEI+PPD / TMC membrane, the peak at 1254 cm -1 A peak attributed to S=O stretching vibration was observed at .

[0067] Figure 2 (c)-(f) in the figure are XPS scanning spectra of PEI+PPD-TMC film, where (c) is the full spectrum of PEI+PPD-TMC film, (d) is the C1s peak of PEI+PPD-TMC film, (e) is the N1s peak of PEI+PPD-TMC film, and (f) is the O1s peak of PEI+PPD-TMC film. Figure 2 As can be seen from (c)-(f) in Figure 3, C, N, and O elements are displayed in all XPS wide scan spectra. However, due to the presence of the HPAN support under the polyamide membrane, it inevitably interferes with the C1s spectrum. Therefore, the CC chemical nature of the HPAN support can also be observed, and after the formation of the polyamide membrane, another peak is observed at 398.8eV, which is attributed to O=CN, indicating that an interfacial cross-linking reaction occurs between the amine and the acyl chloride. On the other hand, the polyamide HPAN membrane has a very significant peak corresponding to O1s, which can be deconvoluted to NC=O (530.4eV) chemistry, indicating that the polyamide membrane is formed on the HPAN substrate. The above results indicate that PEI and PPD are successfully cross-linked with TMC to form a separation layer. In addition, the appearance of CO was observed at 531.4eV of O1s, which is attributed to the ester bond formed by the reaction between the hydroxyl group of IPA and the acyl chloride. In order to evaluate the relationship between the properties of the membrane separation layer and the flux, the water contact angle, EtOH contact angle, and surface Zeta potential of the membrane were studied. The adsorption and dissolution of solvent permeable molecules mainly depend on the hydrophilic / hydrophobic properties of the membrane surface.

[0068] like Figure 2 (g) is the water contact angle of PEI / TMC, PPD / TMC and PEI+PPD / TMC, Figure 2(h) in the figure is the ethanol contact angle of PEI / TMC, PPD / TMC and PEI+PPD / TMC. For PEI / TMC, PPD / TMC and PEI+PPD / TMC, the surface water contact angles of the membranes were 16.33°, 34.22° and 24.54°, respectively, and the surface alcohol contact angles were 16.39°, 34.22° and 24.29°. Although the wettability of the PPD / TMC membrane was slightly reduced due to the introduction of the hydrophobic benzene ring of PPD, the prepared membranes all showed high wettability due to the rich amine groups. The ultra-low angle of the PEI+PPD / TMC membrane lays the foundation for the high permeability of subsequent solvents.

[0069] Figure 2 (i) is the Zeta potential of the PEI+PPD / TMC membrane, which is used to evaluate the effect of pH on the membrane surface charge. The polyamide membrane prepared with PEI and PPD as the amine source carries a large number of amine groups on its surface. The results show that compared with the Zeta potential of the HPAN membrane (-10.3mV), the obtained PEI+PPD / TMC membrane exhibits a positive surface charge intensity (pH = 7, Zeta potential is 10.69mV).

[0070] 2. Morphology and structure of PEI / TMC, PPD / TMC, and PEI+PPD / TMC membranes

[0071] The microstructure of the composite membrane surface is related to the separation performance. In order to observe the internal structure of the composite membrane more clearly, the surface and cross-section of the separation layer formed on the HPAN substrate were analyzed using SEM and AFM. Figure 3 The SEM images of the surface and cross section of different TFC membranes are shown in Figure 2. Figure 3 It can be seen that due to the different amine monomers used, the structure of the polyamide layer formed on the membrane surface is also different. Figure 3 (a) is the surface of the PEI / TMC membrane. It can be seen that the surface morphology of the membrane is similar to a bubble structure, while the surface of the PPD-TMC membrane is distributed as an uneven nodular structure ( Figure 3 (b) in the Figure 3 (c) is the SEM image of the PEI+PPD / TMC film. It can be seen that when PEI and PPD are added simultaneously, larger nodules are formed on the membrane surface, resulting in the appearance of wrinkles. In addition, since SDBS is added during the preparation of the membrane, the presence of benzene rings in the structure of this surfactant makes the layer somewhat loose due to its large structure.

[0072] In the IP reaction, the concentration of monomers plays an important role in the structure and performance of the prepared nanofiltration membrane. Figure 3Figures (c)-(e) show the SEM images of PEI+PPD / TMC membranes at 0.15wt% (M1), 0.05wt% (M3) and 0.25wt% TMC (M5) concentrations, respectively. It can be seen that the surface density of the composite membrane increases with the increase in TMC monomer concentration. The above phenomenon is due to a greater degree of crosslinking.

[0073] In addition, the thickness of the polyamide membrane was analyzed from the cross-sectional morphology of the TFC membrane. Figure 3 Figures (f)-(h) are cross-sections of PEI+PPD / TMC membranes at TMC concentrations of 0.15wt%, 0.05wt%, and 0.25wt%, respectively. It can be seen from Figures (f)-(h) that all membranes form a continuous and uniform PA skin layer on the top layer of the finger-like structure of the HPAN substrate, and the thickness of the formed PA thin layer is about <100nm. In addition, the thickness of the polyamide membrane gradually increases with the increase of TMC concentration. Since more TMC molecules participate in the IP reaction, which is conducive to the growth of the polyamide layer, the formation of a thin layer on the membrane support causes the surface to shrink completely, resulting in excellent separation performance.

[0074] Figure 3 (i) in Figure 3 depicts a 3D AFM image of a PEI+PPD / TMC film. It can be seen that when the polyamide layer is deposited on the support, the resulting film has a rough surface with Ra=33.1 nm.

[0075] 3. Study on the organic solvent nanofiltration performance of PEI / TMC, PPD / TMC, and PEI+PPD / TMC membranes (M1)

[0076] 1) To understand the relationship between membrane structure and separation performance, membrane selectivity and permeability were evaluated using acid fuchsin (AF) solution. The type of amine solvent and the concentration of each monomer (PEI, PPD, and TMC) were systematically studied to determine the optimal conditions for synthesizing high-performance TFC membranes for dye separation and drug purification.

[0077] In order to ensure the dissolution of PEI and PPD, common alcohol organic solvents (methanol (MeOH), ethanol (EtOH), isopropanol (IPA), n-butanol (NBA), ethylene glycol (MEG), V 甲醇 / V 水 =1:1 mixed solvent or V 乙醇 / V 水 =1:1 mixed solvent) or water as the amine solvent for IP. Figure 4 (a) shows the effect of different solvents on the performance of PEI+PPD / TMC membrane. The experimental results show that when IPA is used as the amine solvent, the rejection rate is 95.12% and the permeability is 46.44 L·m -2 ·h-1 bar -1 , the overall performance is significantly improved compared to water as a solvent. The Hildebrand solubility parameter is a good indicator of the ability of certain solutions to act as membrane solvents. A comparison of the solubility parameters between these alcohols and polyamide membranes shows that the solubility parameter for IPA is 23.5 MPa 1 / 2 , closest to polyamide membrane (23MPa 1 / 2 ). This suggests that compared with other alcohols, isopropanol is more likely to penetrate the newly formed polyamide layer, thereby reacting with the acyl chloride to form ester bonds, ending the growth of some polyamide molecular chains, reducing the cross-linking degree of the network polyamide, and the separation layer of the composite membrane is looser than before, resulting in increased permeability ( Figure 4 (f) in). However, ethylene glycol is a polyhydroxy solvent, and ethylene glycol has a stronger polarity and is immiscible with n-hexane of lower polarity. Compared with amine monomers with better oil solubility, the chance of reacting with TMC at the interface is much higher, resulting in a reduced density of the 3D network, a reduced rejection rate, and an increased flux. Therefore, the present invention selects isopropanol as an amine solvent for subsequent research.

[0078] Reactive monomer concentration plays a key role in the preparation of PEI+PPD / TMC membranes. In order to reveal its influence, the present invention continues to study the influence of PEI, PPD and TMC concentrations on the nanofiltration performance of PEI+PPD / TMC membranes. Figure 4 As shown in (b), (c) and (d). Figure 4 (b) shows the effect of different PEI concentrations on the performance of PEI+PPD / TMC membrane. Figure 4 (c) shows the effect of different PPD concentrations on the performance of PEI+PPD / TMC membrane. Figure 4 (d) shows the effect of different TMC concentrations on the performance of PEI+PPD / TMC membrane. Figure 4 As can be seen from (a) in the figure, with the increase of PEI monomer concentration, the permeability of the membrane gradually decreases and the retention rate increases. This is caused by the gradual increase of cross-linking degree. Under normal circumstances, the effect of PPD monomer concentration on membrane performance should also follow this law. However, when the PPD concentration increases from 2wt% to 3wt%, the retention rate will decrease from 92.81% to 83.58%, because the solubility of PPD in IPA solvent becomes smaller, and there is precipitation during the experiment, which may affect the performance of the membrane (see Figure 4(c) in the figure). When the concentration of TMC increases from 0.05wt% to 0.25wt%, the permeability shows a trend of first increasing and then decreasing. This is because the diffusion of monomers in IP is closely related to concentration. When the concentration of TMC is low, the IP reaction is prolonged, and the TMC molecules in n-hexane diffuse more slowly into IPA, resulting in a thicker PA layer. This inevitably leads to an increase in the resistance of the solute. When the concentration of TMC increases further, it diffuses rapidly and reacts quickly with the amine monomers to form a sufficiently dense PA layer, which prevents the diffusion of monomers and inhibits subsequent reactions. Therefore, a thinner PA membrane can be obtained in this rapid process, but if the concentration of TMC is too high, the TMC molecules no longer participate in the reaction and remain in the membrane channels, resulting in a decrease in permeability (see Figure 4 (d) in the figure.

[0079] UV-visible absorption spectra of AF solution before and after filtration Figure 4 As shown in (e), it is shown that PEI+PPD / TMC (M1) can effectively separate AF. In the present invention, when 3 wt% PEI, 2 wt% PPD and 0.15 wt% TMC are dissolved in IPA solvent, the composite membrane has good separation performance and the highest retention rate is 98.2% (see Figure 4 (d) in the figure shows that the highest permeability is 46.44 L·m -2 ·h -1 bar -1 (See Figure 4 (a) in the figure.

[0080] 2) The AF inhibition performance of PEI / TMC, PPD / TMC and PEI+PPD / TMC membranes was compared when IPA was used as solvent. Figure 5 (a) is a comparison of the properties of PEI / TMC, PPD / TMC and PEI+PPD / TMC membranes with acid fuchsin in EtOH. Figure 5 As can be seen from (a), the TFC membrane performance of PEI / TMC and PPD / TMC is not as good as that of PEI+PPD / TMC. PEI is a flexible substance, and the membrane formed by interfacial polymerization with TMC is dense, but compared with PPD, it contains more primary amines, secondary amines and tertiary amines, so it has good hydrophilicity. Paraphenylenediamine contains a rigid benzene ring structure, with two amino groups in the para position in the molecule, and no other substituents on the benzene ring. The structure is rod-shaped, which is easy to form a compact structure, and produces a 1+1>2 effect when combined.

[0081] Five dyes, namely Bengal red (RB), Congo red (CR), acid fuchsin (AF), chrome black T (EBT), and calcein (Calcein), were used for separation tests to obtain the accurate separation performance of the PEI+PPD / TMC membrane. Figure 5As shown in (b), in the membrane with the best performance, the retention rates of RB, CR, AF, EBT and Calcein are 96.63%, 95.98%, 95.21%, 93.84% and 85.79%, respectively. Calcein is a cell staining reagent that is insoluble in EtOH but soluble in EtOH-water mixed solution. This is why the corresponding flux is reduced to 10.77 L·m -2 ·h -1 bar -1 . It has excellent rejection properties for dyes with a molecular weight (Mw) above 600Da. For RB and CR, the rejection of dyes mainly depends on their molecular size. When the dye molecules have similar molecular sizes, the rejection of the dyes is mainly determined by the Zeta potential. The Zeta potential shows that the membrane has a positive charge of 10.69mv, which proves that electrostatic mutual attraction plays an important role in the separation process of the membrane. The results show that the separation mechanism of PEI+PPD / TMC membrane is controlled by sieving size and charge, and this ability to identify different molecular sizes can be applied to the separation of specific molecules in mixed solutions. Figure 5 As shown in (c) and (d), AF is rejected, while MO passes through the membrane and enters the permeate solution. Therefore, the feed solution can be obtained by mixing the macromolecular dye AF with the small molecule dye methyl orange (MO).

[0082] The present invention also studies the separation performance of PEI+PPD / TMC membrane for small drug molecules. W Sodium fluorescein and chlorogenic acid are 376.27Da and 354.31Da, respectively. They have good separation performance, with retention rates of 88.19% and 80.41%, respectively, which indicates that PEI+PPD / TMC membrane also has good application prospects in mixed drug solutions. Therefore, a mixture of sodium fluorescein and berberine hydrochloride was selected (see Figure 5 (e) and (f) in Figure 5. Figure 5 (g) in the figure is the ultraviolet spectrum of the separation performance of berberine hydrochloride and sodium fluorescein. The positively charged berberine hydrochloride can easily pass through the membrane, while the negatively charged sodium fluorescein stays on the membrane surface through electrostatic action to achieve the purpose of separation.

[0083] In the nanofiltration of organic solvents, the wide applicability of the membrane in organic solvents is worth exploring. Figure 5The flux of PEI+PPD / TMC membrane for n-butanol (NBA), isopropanol (IPA), ethanol (EtOH), H2O, methanol (MeOH), ethyl acetate (EA) and acetone (ACE) increased in sequence, which were 26.68, 34.17, 55.46, 62.51, 75.93, 79.92 and 98.83 L·m -2 ·h -1 bar -1 The regular increase in this flux is to some extent related to the solubility parameters, viscosity and kinetic diameter of the solvent itself. Figure 5 As shown in (i), the solvent permeability of the PEI+PPD / TMC membrane is linearly related to 1 / η, indicating that the solvent transport is consistent with the porous membrane. Solvent viscosity plays an important role in the migration of polar solvents in hydrophilic membranes. Solvent permeability decreases with increasing solvent viscosity. Ultra-low viscosity makes non-polar solvents such as EA and ACE super permeable. In addition, the ethanol-philic surface of the PEI+PPD / TMC membrane also promotes the penetration of non-polar solvents.

[0084] 4. Stability test of PEI+PPD / TMC (M1) membrane

[0085] Stability is an important parameter for membranes. To explore the stability of PEI+PPD / TMC nanofiltration membranes, Bengal Red (RB) alcohol solution was used to perform a long-term operation test at a pressure of 1 bar for up to 500 minutes. The results are as follows: Figure 6 As shown in (a), it can be seen that at the beginning, due to the continuous compaction of the nanofiltration membrane, the flux will decrease. As time goes by, the flux stabilizes at 39.35 L·m -2 ·h -1 bar -1 After 440 minutes of operation, the retention rate of the membrane dropped to below 90%. The performance of the membrane remained within an acceptable range during long-term operation, and it had good long-term operation stability.

[0086] The membrane needs to withstand a certain high pressure environment during actual use, so the performance changes of the PEI+PPD / TMC membrane under different pressures were tested, such as Figure 6 As shown in (b), as the pressure increases from 1 bar to 5 bar, the retention rate gradually decreases from 97.45% to 92.03%. Although there is a slight decrease, there may be accumulation of RB macromolecules on the membrane surface during this process, causing membrane fouling pores and a decrease in flux. However, the overall RB separation ability is still maintained, proving that the PEI+PPD / TMC membrane has the ability to be used under high pressure.

[0087] In addition, the present invention also tests the performance change of the PEI+PPD / TMC membrane during the cyclic use process. First, the membrane is passed through RB at a pressure of 2 bar for 30 minutes, and then it is immersed in an ethanol solution for 30 minutes. At the same time, the stability of the membrane is determined by calculating the recovery rate of water flux and the retention rate of dye in each cycle. Figure 6 As shown in (c), after 6 cycles, the retention rate of PEI+PPD / TMC membrane will be partially reduced, which may be caused by membrane pore collapse, separation of separation layer and substrate, and membrane pore blockage after multiple cycles. In general, PEI+PPD / TMC nanofiltration membrane has good long-term use ability, pressure resistance and recycling ability, and the infrared spectrum of the membrane surface after long-term use was tested. Figure 6 (f) is the infrared spectrum of the PEI+PPD / TMC membrane before and after 6 cycles. It can be seen that the characteristic peak of polyamide in the separation layer of the PEI+PPD / TMC membrane has hardly changed.

[0088] Finally, the performance of PEI+PPD / TMC membrane in separating small and medium-molecule dyes in different organic solvents was studied, which proved that the membrane had good solvent resistance. Figure 6 Figure (d) and Figure (e) are schematic diagrams of the separation mechanism. The fluxes are 56.14, 20.62, and 11.94 L·m -2 ·h -1 bar -1 , corresponding to the solvent viscosity, the retention rates were 90.89%, 85.42% and 95.86%, respectively, all maintaining a good level.

[0089] PEI+PPD / TMC was immersed in ethanol for 5 days, and the changes in the membrane surface morphology were observed using a scanning electron microscope. Figure 6 (g) is before immersion, and (h) is after immersion. It can be seen that the polyamide structure on the surface of the membrane does not change much before and after immersion in EtOH for 5 days, proving that the membrane has good applicability in nanofiltration of organic solvents. Compared with the results in other literatures, it is found that the ethanol flux of the TFC membrane in the present invention is 3-20 times that in the literature (see Figure 6 (i)), indicating that IPA as a solvent can produce a fairly high-flux OSN membrane through IP reaction.

[0090] in conclusion

[0091] In summary, the present invention proposes an isopropanol-assisted interfacial polymerization method to prepare PEI+PPD / TMC membranes. The preparation method is simple and easy to operate. The successful formation of a polyamide separation layer on the HPAN substrate was demonstrated by various characterizations. The effects of PEI concentration, PPD concentration, and TMC concentration during the interfacial reaction on the OSN performance of the TFC membrane were studied. Compared with the traditional TFC membrane, the ethanol permeability of the optimal TFC membrane can reach 46.44 L·m -2 ·h -1 bar -1 The possible reason is that the affinity of isopropanol makes it easier to penetrate the nascent polyamide membrane and react with acyl chloride to form ester bonds, thereby terminating the extension of the polyamide chain and making the membrane looser. And due to chemical thermal crosslinking, PEI+PPD / TMC shows good stability and solvent resistance. Therefore, this work may provide a more effective strategy for designing high-performance TFC membranes with great potential in OSN applications.

[0092] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a polyamide organic solvent nanofiltration membrane, characterized in that: The following steps are involved: Weighing polyethyleneimine, p-phenylenediamine and sodium dodecylbenzenesulfonate, adding them to an isopropanol solution, and ultrasonically treating them until dissolved to obtain an amine solution; soaking a dried HPAN support membrane in the amine solution for reaction, taking it out and drying it at room temperature; The dried membrane is placed in a n-hexane solution of trimesoyl chloride for reaction, and then taken out for cross-linking reaction to obtain a polyamide organic solvent nanofiltration membrane.

2. The method for preparing a polyamide organic solvent nanofiltration membrane according to claim 1, characterized in that: The HPAN support membrane reacts in the amine solution for 10 minutes.

3. The method for preparing a polyamide organic solvent nanofiltration membrane according to claim 1, characterized in that: The dried film was reacted in a n-hexane solution of trimesoyl chloride for 10 min.

4. The method for preparing a polyamide organic solvent nanofiltration membrane according to claim 1, characterized in that: The specific preparation method of the HPAN membrane is as follows: Adding polyacrylonitrile and polyvinyl pyrrolidone into N,N-dimethylformamide solution to dissolve, to obtain a light yellow transparent viscous liquid; leaving the light yellow transparent viscous liquid to stand at room temperature to defoam, to form a uniform casting solution; pouring the casting solution on a non-woven fabric to form a film, and immersing the film in deionized water to form a PAN film; The PAN membrane is immersed in a NaOH solution for hydrolysis to obtain an HPAN membrane; the HPAN membrane is rinsed with deionized water until it becomes neutral, thereby obtaining an HPAN support membrane.

5. The method for preparing a polyamide organic solvent nanofiltration membrane according to claim 1, characterized in that: The concentration of the polyethyleneimine in the isopropanol solution is 1-5wt%; the concentration of the p-phenylenediamine in the isopropanol solution is 1-3wt%; and the concentration of the sodium dodecylbenzene sulfonate in the isopropanol solution is 0.1wt%.

6. The method for preparing a polyamide organic solvent nanofiltration membrane according to claim 1, characterized in that: The concentration of the trimesoyl chloride solution is 0.05-0.25 wt %.

7. The method for preparing a polyamide organic solvent nanofiltration membrane according to claim 1, characterized in that: The cross-linking reaction is carried out at 80° C. for 10 minutes.

8. A polyamide organic solvent nanofiltration membrane prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the polyamide organic solvent nanofiltration membrane as claimed in claim 8 in wastewater treatment.

10. The use according to claim 9, characterized in that: The wastewater is wastewater containing organic dyes.